(untitled) (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2021)
Studies on the isolation of nucleic acids from the internal organs of rodents were carried out at the Institute of Biotechnology of the National Academy of Sciences of the Kyrgyz Republic in the laboratory of biotechnology and nutrition. The aim of this study was to study methods for the isolation of nucleic acids from the internal organs of rodents. In the course of the research, the methods of DNA and RNA isolation from different samples of biological objects were mastered. The method of qualitative and quantitative accounting of DNA and RNA isolated from samples was carried out using a Nano Drop 2000 spectrophotometer. According to the results of the study, 25 DNA samples and 24 RNA samples had admissible concentrations 84,3 – 630,5 9, which made it possible to use them for further research.